W12 [Tell Your Senators: "Enough is Enough"] - POOLE,J (Tufts Archival Research Center, 2007)
Copy; Missing Attachments; Memorandum to Philip Morris, USA employees urging them to contact their Senators, asking them to oppose excise tax as means of financing healthcare reform. Explains the potential excise tax and negative effect on business. Includes an attachment with specific writing points to use in contacting Senators.